Discovering C3 targeting therapies for paroxysmal nocturnal hemoglobinuria: Achievements and pitfalls. (January 2022) - Risitano, Antonio M.; Peffault de Latour, Regis; Marano, Luana; Frieri, Camilla
Abstract: The treatment of paroxysmal nocturnal hemoglobinuria (PNH) was revolutionized by the introduction of the anti-C5 agent eculizumab, which resulted in sustained control of intravascular hemolysis, leading to transfusion avoidance and hemoglobin stabilization in at least half of all patients. Nevertheless, extravascular hemolysis mediated by C3 has emerged as inescapable phenomenon in PNH patients on anti-C5 treatment, frequently limiting its hematological benefit. More than 10 years ago we postulated that therapeutic interception of the complement cascade at the level of C3 should improve the clinical response in PNH. Compstatin is a 13-residue disulfide-bridged peptide binding to both human C3 and C3b, eventually disabling the formation of C3 convertases and thereby preventing complement activation via all three of its activating pathways. Several generations of compstatin analogs have been tested in vitro, and their clinical evaluation has begun in PNH and other complement-mediated diseases. Pegcetacoplan, a pegylated form of the compstatin analog POT-4, has been investigated in two phase I/II and one phase III study in PNH patients. In the phase III study, PNH patients with residual anemia already on eculizumab were randomized to receive either pegcetacoplan or eculizumab in a head-to-head comparison. At week 16, pegcetacoplan was superior to eculizumab in terms of hemoglobin change from baseline (the primary endpoint), as well as in other secondary endpoints tracking intravascular and extravascular hemolysis. Pegcetacoplan showed a good safety profile, even though breakthrough hemolysis emerged as a possible risk requiring additional attention. Here we review all the available data regarding this innovative treatment that has recently been approved for the treatment of PNH. Highlights: C3-mediated extravascular hemolysis limits the hematological benefit of anti-C5 treatment in PNH. Strategies involving C3-targeting therapeutic inhibition have been developed to improve the current treatment of PNH. Pegcetacoplan is a small peptide C3 inhibitor that has been found to be safe and effective in two Phase II trials in PNH. In a Phase III randomized trial, pegcetacoplan was superior to eculizumab in terms of hemoglobin response. Pegcetacoplan treatment was safe and effective, with breakthrough hemolysis as the only potential complication.